Human Resource Management in Enhancing Teacher Competence: A Case Study at Elementary School 25 Kinali, West Pasaman Regency - Yuharnis, Yuharnis; Erni, Yusnizar; Gistituati, Nurhizrah; Nellitawati, Nellitawati; Achyar, Novriyanti (International Journal of Educational Dynamics, 2024)
This article presents the findings of a field study conducted at Elementary School 25 Kinali, focusing on human resource management strategies to enhance teacher competence. The study addresses challenges related to insufficient teaching competencies among teachers, which have resulted in disruptive student behavior, such as talking during lessons, disturbing peers, and frequently leaving the classroom without permission. The study employs a qualitative descriptive method with a phenomenological approach, utilizing data collection techniques such as observation, in-depth interviews, and documentation. Data analysis was conducted through processes of data reduction, data presentation, and conclusion drawing, with the validity of findings ensured through data triangulation. The results indicate that human resource management plays a critical role in improving teacher competence through key activities, including planning, organizing, and conducting teacher training programs.